A stable Fe/Co bimetallic modified biochar for ofloxacin removal from water: adsorption behavior and mechanisms. Issue 49 (4th November 2022) - Hao, Jiajie; Wu, Lieshan; Lu, Xiaowei; Zeng, Yalin; Jia, Bing; Luo, Tingting; He, Shixing; Liang, Liuling
Abstract : Fe/Co bimetallic modified biochar (FMBC) was synthesized and characterized, and its adsorption mechanism of ofloxacin and the stability of FMBC were investigated. Abstract : In this study, Fe–Co-modified biochar (FMBC) loaded with iron (Fe) and cobalt (Co) bimetals after NaOH activation was prepared by pyrolysis using forestry waste cedar bark as a raw material to study its properties and the adsorption of ofloxacin (OFX). The surface structure and chemical properties were analyzed by BET, SEM-EDS, XRD, XPS, and FTIR characterization, and the results showed that the FMBC possessed a larger specific surface area and abundant surface functional groups. FMBC conformed to pseudo-second-order kinetic and Langmuir isotherm models, indicating that the OFX adsorption process on FMBC was a monolayer adsorption process and controlled by chemisorption. The saturation adsorption capacity of FMBC was 10 times higher than that of cedar bark biochar (BC). In addition, the effects of initial pH and coexisting ions on the adsorption process were investigated, and FMBC showed good adsorption, with the best adsorption capacity at pH = 7. Multiple adsorption mechanisms, including physical and chemical interactions, were involved in the adsorption of OFX by FMBC. TG, metal leaching, different water sources, and VSM tests showed that FMBC had good stability and was easily separated from water. Finally, the reusability performance of FMBC was investigated by various methods, and after five cycles it could still reach 75.78–89.31% of the adsorption capacity before recycling. Therefore, the FMBC synthesized in this study is a promising new adsorbent.